31. DIRECT MEDICAL COSTS IN THE TREATMENT OF HEART FAILURE AT SOME HOSPITALS IN NORTHERN VIETNAM IN 2023: AN ANALYSIS FROM THE PERSPECTIVE OF HEALTH SYSTEM (Vietnam Journal of Community Medicine, 2025)
Objectives: To analyze the direct medical cost of heart failure treatment at several hospitals in Northern Vietnam.Methods: This multi-center cross-sectional retrospective study collected data from electronic medical records and cost schedules, applying a healthcare system perspective.Population: Patients with heart failure were treated at 03 Provincial General Hospital (Phu Tho, Vinh Phuc, and Lang Son) from January 1st, 2023, to December 31st, 2023.Results: The average cost per outpatient visit was VND 564,613 ± 346,640, with the medication and infusion cost accounting for the greatest proportion (60.0%). The average cost per admission which lasted 6.3 ± 5.2 days, was VND 7,083,868 ± 13,000,390, with the cost for room and board representing the highest proportion (22.4%). Health insurance covered more than 90% of the total costs.Conclusion: The average cost per outpatient visit and the average cost per admission found in this study were lower than those from previous studies which may be influenced by different study locations. Further research should consider applying more comprehensive perspectives.
Keywords: hearth failure; cost; health system